Proceedings of the 2023 ACM Designing Interactive Systems Conference 2023
DOI: 10.1145/3563657.3596109
|View full text |Cite
|
Sign up to set email alerts
|

Understanding how to Design Health Data Visualizations for Chilean Older Adults on Mobile Devices

Gabriela Cajamarca,
Valeria Herskovic,
Stephannie Dondighual
et al.

Abstract: Mobile devices, including activity trackers and smartwatches, can help older adults monitor health parameters passively and unobtrusively. Most user interactions with small devices consist of brief glances at the time or notifcations. Consuming information from small displays poses challenges, which have been seldom studied from the perspective of older users. In this paper, we worked with older adults towards creating health data visualizations for them for small devices. We conducted a mixed-methods study wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Several empirical studies (e.g., [JHG*12,WM12,MSC*19]) advocate for the adoption of simple and high data‐ink ratio visualizations as a means to alleviate cognitive load and demand on older adults. In a participatory design project conducted by Cajamarca et al [CHD*23], older adults expressed their preference for health data apps on smartwatches to have “familiar,” “clear,” and “clean” designs. In two separate studies, Le et al [LRY*15, LCC*18] also found that older adults tended to focus on aggregate measures and data overviews unless trying to explain an observed pattern or change, indicating that older adults' information‐seeking behavior may conform to Schneiderman's visualization mantra “overview first, details on demand” [Shn03].…”
Section: State Of the Practice In Gerontovismentioning
confidence: 99%
See 1 more Smart Citation
“…Several empirical studies (e.g., [JHG*12,WM12,MSC*19]) advocate for the adoption of simple and high data‐ink ratio visualizations as a means to alleviate cognitive load and demand on older adults. In a participatory design project conducted by Cajamarca et al [CHD*23], older adults expressed their preference for health data apps on smartwatches to have “familiar,” “clear,” and “clean” designs. In two separate studies, Le et al [LRY*15, LCC*18] also found that older adults tended to focus on aggregate measures and data overviews unless trying to explain an observed pattern or change, indicating that older adults' information‐seeking behavior may conform to Schneiderman's visualization mantra “overview first, details on demand” [Shn03].…”
Section: State Of the Practice In Gerontovismentioning
confidence: 99%
“…In addition to investigating various use cases of data visualization in health care, these also offer valuable insights that can inform the design of visualizations for older adults. For instance, Ahmed et al [ATRG*19] observed that older adults consistently removed a sad‐looking face emoji from a heart health dashboard due to its negative connotation and concluded that such designs may discourage continued use, while Cajamarca et al [CHD*23] observed that older adults preferred health visualizations that instilled tranquil feelings. While studying how older adults would use data visualizations for self‐assessment of their abilities to use a computer mouse, Jones et al [JHG*12] observed that participants noticeably found charts depicting hypothetical unwanted health scenarios to be unfavorable and avoided interacting with them.…”
Section: State Of the Practice In Gerontovismentioning
confidence: 99%
“…While prior work on glanceable visualization and aging is remarkably sparse [14], the existing literature provides a starting point that informs and motivates this study. In this section, we discuss relevant current work on glanceable visualization (Section 3.1), visualizations for older adults (Section 3.2), as well as smartwatches and older adults (Section 3.3).…”
Section: Related Workmentioning
confidence: 99%
“…Fan et al [23] identified challenges for older adults in understanding interactive COVID-19 data visualizations, such as insufficient information clarity. Additionally, Cajamarca et al [14] observed that older Chilean adults interpreted health data on smartwatches more accurately without progress indicators, which otherwise distracted them from essential information. They also found that older adults with higher technology proficiency had better accuracy and speed in data interpretation.…”
Section: Visualization and Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation